Anesthetic-, irrigation- and pain-free dentistry? The case for a femtosecond laser enabled intraoral robotic device - Rapp, Ludovic; Madden, Steve; Rode, Andrei V.; Walsh, Laurence J.; Spallek, Heiko; Nguyen, Quan; Dau, Van; Woodfield, Peter; Dao, Dzung; Zuaiter, Omar; Habeb, Alaa; Hirst, Timothy R. (Frontiers in Dental Medicine, 2022)
By leveraging ultrashort pulse laser and micro-electromechanical systems (MEMS) technologies, we are developing a miniaturized intraoral dental robotic device that clamps onto teeth, is remotely controlled, and is equipped with a focusing and scanning system to perform efficient, fast, and ultraprecise laser treatments of teeth and dental restorative materials. The device will be supported by a real-time monitoring system for visualization and diagnostic analysis with appropriate digital controls. It will liberate dentists from repetitive manual operations, physical strain and proximity to the patient's oropharyngeal area that potentially contains infectious agents. The technology will provide patients with high-accuracy, minimally invasive and pain-free treatment. Unlike conventional lasers, femtosecond lasers can ablate all materials without generating heat, thus negating the need for water irrigation, allowing for a clear field of view, and lowering cross-infection hazards. Additionally, dentists can check, analyze, and perform precise cutting of tooth structure with automatic correction, reducing human error. Performing early-stage diagnosis and intervention remotely will be possible through units installed at schools, rural health centers and aged care facilities. Not only can the combination of femtosecond lasers, robotics and MEMS provide practical solutions to dentistry's enduring issues by allowing more precise, efficient, and predictable treatment, but it will also lead to improving the overall access to oral healthcare for communities at large.